(untitled) (Revista Internacional de Folkcomunicação, 2018)
The study of exvotos as an object of research in the area of communication is at the origin of the theory founded by Luiz Beltrão, Folkcommunication. However, researchers still find difficulties in the typological classification of exvotos. Beltrão does not make an exclusive classification of the exvotos, but they fit them in the general typology of the folkcommunicational studies. The typology adopted today is that elaborated by the Mexican researcher Jorge González (1981), which is restricted to the cultural manifestations of popular Catholicism. Professor José Marques de Melo, writing on the subject, says that the issue is not defined, leaving open a possible reclassification. The objective of this article is the attempt to broaden the understanding, to group and to update the types of exvotos, opening horizons even to other religious manifestations that do not fit into the popular Catholicism, but that can be understood within this communicational process, today on the margins of the academy. The methodology used was the bibliographical and documentary research, as well as the inventory through participant observation. Exvoto. Typology. Folkcommunication. Religions.